THE INFLUENCE OF PRICE, PROMOTION, AND INNOVATION ON PURCHASE DECISIONS OF WAKAROROS BATIK IN OLSABARA SANGATTA: Meita Sondang Riski : meitasondang2@gmail.com STIE Nusantara Sangatta - sondang, meita (STIE Madani Balikpapan, 2025)
Wakaroros Batik is a motif inspired by the Dayak culture, which describes their views on the natural environment using shades of orange, green, pink, and red. In the price marketing system, promotion and innovation is a factor that has been sought by the company but has yet to be able to provide a maximum contribution to consumer decisions. This study aimed to determine the effect of price, promotion, and innovation on purchasing decisions for Batik Wakararoros at Olsabara Sangatta. The study results indicate that price, and innovation positively and significantly impact purchasing decisions for Batik Wakararos at Olsabara Sangatta. Only promotions whose results are not significant.